2017
DOI: 10.15376/biores.13.1.820-835
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Agave Fiber-Reinforced Polypropylene Composites for Automotive Applications

Abstract: As consumer demand for more fuel-efficient vehicles increases, automakers are looking for innovative ways to reduce the weight of vehicles. Many automotivegrade plastics contain traditional reinforcing fillers, such as glass or talc, to improve the mechanical properties of the material. By replacing these high-density fillers with natural fibers, the material and corresponding weight can be reduced, which results in an improvement of the vehicle fuel economy. The objective of this study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
(27 reference statements)
3
30
0
1
Order By: Relevance
“…Composites reinforced with 30 wt% cellulose have, marginally, the lowest enthalpies. It may be that cellulose was hindering polymer chain movement during heat cycling, as observed by Langhorst et al…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Composites reinforced with 30 wt% cellulose have, marginally, the lowest enthalpies. It may be that cellulose was hindering polymer chain movement during heat cycling, as observed by Langhorst et al…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, its usage in the automotive industry is a central strategy for meeting light weighting and fuel economy standards. Reducing a vehicle's weight by 10% can improve the fuel economy by 3% to 7% and contribute to attaining the CAFE standards. Despite the attractiveness of natural fiber reinforced polymer composites, they exhibit lower modulus and strength as well as inferior moisture resistance compared to synthetic fiber reinforced composites, such as glass fiber reinforced polymer composites …”
Section: Introductionmentioning
confidence: 99%
“…These authors obtained also similar results for flexural properties, that is, mechanical properties remained unchanged for 10% composites, while drastic reductions were observed for 40% composites. Langhost [42] obtained an increase in the flexural properties for injected PP composites with up to 30% of agave fibres (agave tequilana), while a reduction in tensile and impact strength were observed. These authors also found that the use of a compatibilizer, such as grafted PP with maleic anhydride, increases the mechanical properties of the composite.…”
Section: Composites Characterizationmentioning
confidence: 98%
“…It is well known that the interfacial adhesion is one of the key factors to the performance of fiber‐reinforced polymer matrix composites. To obtain high mechanical properties, improving the interfacial adhesion between SGF and polymer matrix is necessary and many efforts have been made . So far, maleic anhydride or glycidyl methacrylate as compatibilizer was used to graft PP which is general method to improve the interfacial adhesion between fibers and matrix .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high mechanical properties, improving the interfacial adhesion between SGF and polymer matrix is necessary and many efforts have been made. [16][17][18] So far, maleic anhydride or glycidyl methacrylate as compatibilizer was used to graft PP which is general method to improve the interfacial adhesion between fibers and matrix. [19][20][21] Sakai group [22] found that lignin derivatives could improve the compatibility of PP and carbon fiber effectively.…”
Section: Introductionmentioning
confidence: 99%